Hubungan antara Grit Terhadap Penyesuaian Diri Siswa Boarding School - Raidah Hanifah; M Mujidin; Ahmad Muhammad Diponegoro (Psyche 165 Journal, 2021)
The transition period for school change has an impact on students. This study aims to determine the relationship between grit and self-adjustment of students who carry out the boarding school program in the tenth grade in Yogyakarta. Using cluster random sampling technique, this research was conducted at three middle schools in tenth grade students who conducted a boarding school program with a total of 117 students. The measuring instrument in this study used a grit scale and a self adjustment scale. Data analysis using mement product correlation. The results showed that the coefficient between grit andself-adjustment was 0.316 with a significance level of 0.001 (p <0.01). It is concluded that there is a very significant positiverelationship between grit and self-adjustment of tenth grade boarding school students in Yogyakarta. So, the higher the grit,the higher the student's adjustment